2015
DOI: 10.2169/internalmedicine.54.4702
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index Is Associated with Hypertension in Japanese Young Elderly Individuals: Findings of the New Integrated Suburban Seniority Investigation

Abstract: Objective This study aimed to investigate the association between BMI at 65 years of age and the development of hypertension during the subsequent five years. Methods A total of 1,003 participants (65 years of age) who had no history of myocardial infarction and/or hypertension at baseline health check-ups (1996-2005) and participated in a secondary health check-up when the subjects reached 70 years of age were analyzed. Results Using fully adjusted models, men with a BMI of <18.5 [odds ratio (OR), 4.08; 95% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 45 publications
(48 reference statements)
2
9
0
1
Order By: Relevance
“…S1. We identified 56 prospective cohort studies , whose characteristics are presented in Table S2. One study reported results for two separate cohort studies and was regarded as two different studies .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…S1. We identified 56 prospective cohort studies , whose characteristics are presented in Table S2. One study reported results for two separate cohort studies and was regarded as two different studies .…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 57 prospective cohort studies with 2,343,466 participants and 216,182 incident cases of HTN were included in meta‐analysis. Twenty studies were from the USA , 13 studies were from Europe , 20 studies were from Asia , 2 studies were from Africa , 1 study was from Mexico and 1 was from Brazil . Baseline characteristics of included studies are presented in Table S2, and reported risk estimates in relation to different categories of anthropometric measures in each study are presented in Table S3.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations